2013
DOI: 10.1159/000351856
|View full text |Cite
|
Sign up to set email alerts
|

Multifocal Central Serous Chorioretinopathy Associated with Steroids in a Patient with Myasthenia Gravis

Abstract: We present a case of bilateral multifocal central serous chorioretinopathy in a 40-year-old male who suffered from myasthenia gravis and was receiving oral prednisolone. Due to the severity of the underlying disease, it was not possible to reduce the corticosteroid dose. After initial unsuccessful treatment with an intravitreal injection of ranibizumab, low-fluence photodynamic therapy was performed, followed by gradual tapering of the corticosteroids. Visual acuity improved significantly in both eyes. Differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
1
3
0
1
Order By: Relevance
“…Long-term steroid use has been suggested not only to increase the risk of CSC but also to cause a more severe bilateral chronic disease with multiple RPE leaking sites, more extended areas of RPE atrophy, and even bullous retinal detachments. 22 24 Piccolino et al 12 have shown that presence of posterior cystoid retinal degeneration, which was considered a sign of severity in our study, is specifically associated with steroid use, longer duration of symptoms, and subretinal fibrin accumulation. Furthermore, severe cCSC presentations were previously described in pregnant women 25 and among certain ethnic groups.…”
Section: Discussionsupporting
confidence: 52%
“…Long-term steroid use has been suggested not only to increase the risk of CSC but also to cause a more severe bilateral chronic disease with multiple RPE leaking sites, more extended areas of RPE atrophy, and even bullous retinal detachments. 22 24 Piccolino et al 12 have shown that presence of posterior cystoid retinal degeneration, which was considered a sign of severity in our study, is specifically associated with steroid use, longer duration of symptoms, and subretinal fibrin accumulation. Furthermore, severe cCSC presentations were previously described in pregnant women 25 and among certain ethnic groups.…”
Section: Discussionsupporting
confidence: 52%
“…Although the aetiology of CSCR are not clearly understood, the condition has been associated with the use of steroids through virtually any route of administration. Furthermore, type A personality, emotional stress, endogenous hypercortisolism as well as an imbalance between sympathetic and parasympathetic activity have also been suggested as risk factors for CSCR [4] . Most cases of acute CSCR resolve spontaneously, but degenerative changes can remain in RPE and the neurosensorial retina of the cases with chronic and recurrent macular detachment, resulting in a poor visual outcome in chronic CSCR cases [3] .…”
Section: Discussionmentioning
confidence: 99%
“…Most cases of acute CSCR resolve spontaneously, but degenerative changes can remain in RPE and the neurosensorial retina of the cases with chronic and recurrent macular detachment, resulting in a poor visual outcome in chronic CSCR cases [3] . Chronic CSCR is often bilateral and occurs more frequently in elderly patients (>50 years) [3,4] . In the first case steroid usage may be associated with CSCR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Daruich a kol. recentně navrhl novou klasifikaci, která jednotlivé (i vzácné) pro-jevy CSC zahrnuje [79] a tato klasifikace je nyní obecně uznávaná [80] Atypická CSC: U pokročilých chronických forem (trvajících několik let) se vedle přetrvávající serózní ablace neuroretiny a mnohačetných atrofických ložisek RPE mohou vyskytovat cystoidní makulární degenerace [76], multifokální CSC [85] či nepravidelné ploché ablace RPE (tzv. wavy RPE), pod kterými se může skrývat již počínající sekundární CNV typu I [86,87].…”
Section: Klasifikace Cscunclassified